Cretaceous–Palaeogene lobsters, Hoploparia stokesi (Weller, 1903), from Antarctica: historical review, and transfer of specimens from the United States Polar Rock Repository - Babcock, Loren E.; Feldmann, Rodney M.; Grunow, Anne M. (Polar research, 2024)
The nephropid lobster Hoploparia stokesi (Weller 1903a) is widely distributed among the islands of the Antarctic Peninsula, where it occurs in strata of Cretaceous (Campanian–Maastrichtian) to Palaeogene (Paleocene) age. Specimens of H. stokesi collected during expeditions in the 1980s that were in the collection of the United States Polar Rock Repository at The Ohio State University have been transferred to the Orton Geological Museum, joining other geological collections from Antarctica. Some of the transferred specimens are voucher specimens described or illustrated in earlier published work.